Religious Intimacies : Intersubjectivity in the Modern Christian West - Moore, Brenna; Dunn, Mary, 1976- (Book collections on Project MUSE., 2020)
"Religious Intimacies examines the history of modern Christianity by exploring intimate bonds through the lens of faith-confessors and penitents, husbands and wives, friends, lovers, and priests. Although many scholars have examined the nature of our ties to others as part of the process of self-formation, religious scholarship has remained inattentive to the power of these intimate bonds. In this collection of essays, each contributor considers a moment in Christian history, examining how intimate relationships intertwined with modern Christianity and Western power and politics. In doing so, editors Mary Dunn and Brenna Moore recast our understanding of modern Christianity by placing interpersonal relationships at the forefront of understanding our relationship to the divine"--